Rheological Behaviour of SiO2/PAO Nanolubricant for an Electric-Driven Compressor Automotive Air-Conditioning System - Aminullah, A.R.M.; Azmi, W.H.; Ramadhan, Anwar Ilmar (Automotive Experiences, 2026)
Compressor lubricants play a crucial role in refrigeration systems by controlling friction, sealing effectiveness, and heat removal, with lubricant viscosity a key parameter that affects hydrodynamic losses and energy efficiency. This study aimed to systematically characterise the rheological behaviour of silicon dioxide/polyalphaolefin (SiO₂/PAO) nanolubricants under compressor operating conditions. SiO₂/PAO nanolubricants with concentrations of 0.01–0.03% were prepared using a two-step method without the use of surfactants, and dynamic viscosity measurements were conducted over a temperature range of 25 to 100 °C and shear rate from 549 to 4320 s⁻¹. The experimental data were further used to understand the viscosity trends under thermal and shear conditions. Both PAO lubricant and SiO₂/PAO nanolubricants exhibited Newtonian rheological behaviour. The incorporation of SiO₂ nanoparticles led to controlled, concentration-dependent changes in viscosity. The 0.01% SiO₂/PAO nanolubricant exhibited the smallest viscosity change (0.7%) even at high temperatures and shear rates, compared with higher concentrations. The findings show that low-concentration SiO₂/PAO nanolubricants, especially at 0.01%, offer good rheological stability with minimal viscosity penalty, providing an advantage to the electric-driven compressor automotive air-conditioning system (EDC-AAC) by reducing compressor work by 3.5%.